Tanggung Jawab Direksi PT Taspen Berdasarkan Hukum Positif Di Indonesia Ditinjau Dengan Prinsip Good Corporate Governance (GCG) - Dhaifina Fadhilah Alyani; Nathania Raissa Putri Rungamali; Nyulistiowati Suryanti; Deviana Yuanitasari (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
A state-owned company has an obligation to implement the principles of Good Corporate Governance (GCG) in order to realize a company that is clean from Ultra Vires actions. However, over time, there are some parties who are not responsible for implementing the GCG principles. The purpose of this research is to see how the responsibility of the Board of Directors towards the implementation of GCG principles and to examine the extent to which the implementation of GCG principles in PT Taspen is carried out. This research uses a normative research method which in its research uses three (3) approaches, namely; statute approach, conceptual approach, and case approach. The intended results are to determine the responsibility of the Board of Directors for the application of GCG principles and to determine the extent to which GCG principles are applied in PT Taspen.